Assessment methods for Bree-type ratcheting without the necessity of linearization of stresses and strains. (January 2015) - Fujioka, Terutaka
Abstract: This paper proposes methods for assessing Bree-type ratcheting in a cylinder subjected to constant internal pressure and cyclic thermal loading. The proposed methods are elastic analysis-route and elastic–plastic analysis-route. The former is based on the polynomial approximation of the elastic stress distributions for thermal stresses and the reference stress concept for estimating primary stress. The latter elastic–plastic route method is based on the concept of relative elastic core size. The methods proposed were validated by performing elastic–plastic finite element analyses of a smooth cylinder that exhibited Bree-type ratcheting. Highlights: Rationalization of the ratcheting assessment has been made. The proposed methods include both elastic and elastic-plastic routes. The elastic route method is based on skeletal point stress by elastic FEA. The elastic-plastic route is based on elastic core size in elastic-plastic FEA. These have been validated by elastic-plastic FEA causing Bree-type ratcheting.